Glaucoma Secondary to Uveitis Due to Posner Schlossman Syndrome (London Journal of Medical and Health Research, 2025)
Considering the clinical relevance of secondary glaucoma due to uveitis in posner-schlossman syndrome (PSS), this study aims to evaluate the natural history of this condition in a patient. To that end, we present the case of a 41-year-old man who experienced hyperemia, mild eye discomfort and decrease in visual acuity in the left eye. The initial ophthalmological examination revealed an intraocular pressure (IOP) of 30 mmhg in the left eye and 19 mmhg in the right, with gonioscopy showing an open angle and trabecular pigmentation. The patient was treated with topical corticosteroids, resulting in normalization of IOP. During follow-up, the patient experienced recurrent episodes of anterior uveitis with IOP ranging from 22 mmhg to 28 mmhg until april 2024. OCT examinations showed thinning of the nerve fiber layer, while visual fields remained normal. Thus, it is observed that early diagnosis and treatment are crucial for the effective management of secondary glaucoma due to uveitis, contributing to the preservation of visual function. It is concluded that rapid intervention with topical corticosteroids is essential to prevent glaucomatous neuropathy secondary to uveitis and to maintain the patient's ocular health.
Keywords: Multiple Trauma; Accidents; Emergency Medicine.; secondary glaucoma; uveitis; posner-schlossman syndrome; intraocular pressure; topical corticosteroids.